আন্তর্জাতিক গনমাধ্যমে মুক্তিযুদ্ধ ও বঙ্গবন্ধু শেখ মুজিব - আর্যু, অস্ট্রিক
Collection of articles and reports from various international newspapers and news magazines on the contribution of Sheikh Mujibur Rahman, 1922-1975, former president of Bangladesh in 1971 liberation war of the country